The influence of apolipoprotein A5 T-1131C and apolipoprotein E common genetic variants on the levels of hemostatic markers in dyslipidemic patients - Novotny, Dalibor; Karasek, David; Vaverkova, Helena; Slavik, Ludek (Clinica chimica acta; international journal of clinical chemistry, 2014)
OBJECTIVES: The aim of this study was to evaluate the relationships of the T-1131C (rs662799) polymorphism variants of apolipoprotein A5 (Apo A5) gene and variants of apolipoprotein E (Apo E) gene common polymorphism (rs429358, rs7412) to selected hemostatic markers. STUDY DESIGN AND METHODS: We examined 590 asymptomatic dyslipidemic patients, subsequently divided into MetS+ (n=146) and MetS- (n=444) groups according to the criteria for identification of the metabolic syndrome (MetS). We compared variant frequencies and differences in levels of hemostatic markers according to Apo A5, Apo E and Apo A5/Apo E common variants. RESULTS: The -1131C Apo A5 minor variant was associated with elevated tissue plasminogen activator (tPA) in comparison to TT genotype (p<0.001), but not in the MetS+ group. The analysis of Apo A5/Apo E common variants in all subjects revealed that the presence of -1131C minor allele has always been associated with higher levels of tPA in comparison with T allele, regardless of Apo E genotype. Also the presence of minor Apo E2 allele led to elevated tPA concentrations in both T and C carriers. In addition, common -1131C/E2 variant was associated with the highest tPA levels. CONCLUSION: We demonstrated a remarkable association especially between the -1131C Apo A5 variant and increased tPA levels in asymptomatic dyslipidemic patients.
Keywords: Apolipoprotein A5; Dyslipidemia; Hemostasis; Dyslipidemias; Male; biologické markery; Middle Aged; Biomarkers; hemostáza; Adult; dospělí; mužské pohlaví; jednonukleotidový polymorfismus; Apolipoprotein E; Tissue Plasminogen Activator; tkáňový aktivátor plazminogenu; Polymorphism, Single Nucleotide; lidé; apolipoproteiny A; dyslipidemie; ženské pohlaví; apolipoproteiny E; asymptomatické nemoci; Metabolic syndrome; Humans; Tissue plasminogen activator; Genetic polymorphism; Asymptomatic Diseases; Female; lidé středního věku; Apolipoproteins A; Apolipoproteins E